IMPLEMENTATION OF TRIAL MANAGEMENT POLICY AT THE MANADO CITY DPRD SECRETARIAT - Merlinda Sumual; Sisca B. Kairupan; Xaverius E. Lobja (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the implementation of the trial management policy at the Manado City DPRD Secretariat and identify supporting factors, obstacles, and strategic steps to improve trial effectiveness. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. The results showed that the implementation of the trial management policy has been running with an adequate regulatory basis (PP No. 12 of 2018 and Permendagri No. 104 of 2018), but is not yet optimal. The communication aspect has used formal and informal channels, but the consistency of information delivery is still hampered by sudden agenda changes. The resource aspect shows the availability of competent human resources and adequate facilities, but the number of staff is limited when the agenda is busy and the budget is less flexible. The disposition aspect reveals a high commitment of administrative staff, but the discipline of DPRD members' attendance remains a structural challenge. The bureaucratic structure aspect has a clear division of tasks, but the coordination mechanism and adaptability of SOPs need to be strengthened. The main supporting factors include regulatory clarity, staff competence, and leadership support, while significant inhibiting factors are agenda uncertainty, lack of quorum, and budget limitations/flexibility. This study recommends the development of an integrated digital system, adaptation of emergency SOPs, optimization of human resources through training, and strengthening cross-departmental coordination to improve the effectiveness of trial management.